2014
DOI: 10.2176/nmc.cr2012-0370
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal Neuralgia Caused by Nerve Compression by Dilated Superior Cerebellar Artery Associated with Cerebellar Arteriovenous Malformation: Case Report

Abstract: Intracranial arteriovenous malformation (AVM) is a rare cause of trigeminal neuralgia (TGN). In this presented case, successful resolution of AVM-related TGN following embolization and gamma knife radiosurgery (GKRS) was obtained. A patient suffered from TGN on the left side, which was thought to be caused by root entry zone compression by dilated superior cerebellar artery (SCA) associated with cerebellar AVM. The cerebellar vermis AVM was embolized in endovascular surgery. The AVM was reduced in size and TGN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…nerve and remits TGN relatively early, suggesting the efficacy of embolization. [9][10][11][12][13] Yuan et al 13) reported that TGN completely resolved 1 week after treatment. It has been reported that even when the responsible blood vessel is a dilated drainer, a similar symptom-improving effect of embolization was acquired.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…nerve and remits TGN relatively early, suggesting the efficacy of embolization. [9][10][11][12][13] Yuan et al 13) reported that TGN completely resolved 1 week after treatment. It has been reported that even when the responsible blood vessel is a dilated drainer, a similar symptom-improving effect of embolization was acquired.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…It has been reported that treatment of nidus reduced blood flow and the size of the feeder, which resolved pulsatile compression of the trigeminal nerve and remitted TGN. 4, [9][10][11][12][13] Since the present case had high-grade AVM, nidus treatment was included in multimodal treatment aiming at elimination of the hemorrhagic risk and treatment of TGN. It was planned to perform excision after multistage embolization and add MVD as the (PCA), and anterior choroidal artery, and the drainers were the great cerebral vein of Galen, basal vein of Rosenthal, and vein of Labbe, and the condition was Spetzler-Martin (SM) grading scale Grade IV (Figs.…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations